2017
DOI: 10.1212/cpj.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Transgender venous thrombosis

Abstract: 53-year-old male-to-female transgender patient on cross-sex hormone replacement therapy (CSHT), estradiol 8 mg daily, presented to the emergency department (ED) with acute-onset headache and left visual field disturbances after a recent mechanical fall with head trauma. The medical history was notable for hyperlipidemia. There was no personal or family history of clotting disorders and no history of tobacco use.In the ED, the patient experienced a generalized tonic-clonic seizure characterized by forced left g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…1,5 CVST can occur in the setting of primary or inherited thrombophilia (antithrombin III, protein C and S deficiencies, and factor V Leiden), acquired thrombophilias such as thrombocytopenia or disseminated intravascular coagulation, trauma, malignancy, dehydration, or changes in hormone levels caused by pregnancy or oral hormonal supplementation with estrogen. [1][2][3][4]6,7 Estradiol is an essential sex steroid in women, mainly secreted from ovarian follicles during the follicular phase of the menstrual cycle. 8 Exogenous estrogen is used for oral contraception, treatment of symptoms related to menopause, IVF, and gender transitioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5 CVST can occur in the setting of primary or inherited thrombophilia (antithrombin III, protein C and S deficiencies, and factor V Leiden), acquired thrombophilias such as thrombocytopenia or disseminated intravascular coagulation, trauma, malignancy, dehydration, or changes in hormone levels caused by pregnancy or oral hormonal supplementation with estrogen. [1][2][3][4]6,7 Estradiol is an essential sex steroid in women, mainly secreted from ovarian follicles during the follicular phase of the menstrual cycle. 8 Exogenous estrogen is used for oral contraception, treatment of symptoms related to menopause, IVF, and gender transitioning.…”
Section: Discussionmentioning
confidence: 99%
“…8 Exogenous estrogen is used for oral contraception, treatment of symptoms related to menopause, IVF, and gender transitioning. 2,3,6 The adverse effects of estrogen are complicated and involve disruption of the balance between procoagulation and anticoagulation factors. 3 Other procoagulant risk factors such as increased age, an underlying preexisting hypercoagulable state, and smoking can synergistically increase the hypercoagulability associated with exogenous hormone use.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, there have been case reports of transwomen presenting with cerebral venous thrombosis in the setting of estrogen GAHT and with no other known risk factors for hypercoagulability. 37,38 Treatment Considerations…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Thromboembolic events were documented as early as the 1970s in MTF-transitioning individuals receiving GAHT. Most studies have reported venous thrombosis or thromboembolism, including deep vein thrombosis with or without pulmonary embolism [ [14] , [15] , [16] , [17] ], cerebral venous thrombosis [ [18] , [19] , [20] ], and retinal vein occlusion [ 21 ]. MTF patients have also presented with arterial thrombosis, including myocardial infarction and ischemic stroke [ 22 , 23 ].…”
Section: Epidemiologic and Clinical Data On Transgender Individualsmentioning
confidence: 99%